EVALUATION OF BONE MINERAL DENSITY USING RADIOGRAPHIC OPTICAL DENSITOMETRY OF PRE AND POSTPUBERTAL BITCHES SUBMITTED TO OVARIOHYSTERECTOMY - Lima, Alfredo F.M. [UNESP]; Luna, Stélio P.L. [UNESP]; Rahal, Sheila Canevese [UNESP]; Tomacheuski, Rúbia [UNESP]; Silva, Bruna Martins [UNESP]; dos Santos, Ivan Felismino Charas [UNESP] (Universidade Federal do Paraná, 2020)
The reduction of gonadal steroid hormone secretion is identified as one of the factors responsible for the decrease in bone mass and, consequently, a decrease in bone mineral density. The study aimed to evaluate the bone mineral density by using radiographic optical densitometry of the distal epiphyseal region of the radius and ulna in prepubertal and post pubertal bitches submitted to ovariohysterectomy (OVH). Thirty-four female dogs were divided into two groups of 16 animals, according with age of neutering: G1 - prepubertal bitches submitted to OVH; G2 - postpubertal bitches submitted to OVH. The animals were submitted to the evaluation of bone mineral density at 24 h before the surgical procedure, 24 and 48 weeks after the surgical procedure. No significant differences in bone mineral density were identified in all groups. Ovariohysterectomy in pre and postpubertal bitches did not induce significant variations in bone mineral density of the distal epiphyseal region of the radius and ulna by using radiographic optical densitometry, during 48 weeks of evaluation.
Avaliação da densidade mineral óssea por meio da densitometria óptica radiográfica de cadelas pré e pós-púbere submetidas à ovariohisterectomia
Keywords: gonadectomy; radio; radiography; small animals; ulna